AKTUALISASI MASYARAKAT KAMPUNG ISLAM KEPAON DI DESA PEMOGAN DENPASAR - Wulandari, Riza (ASKETIK, 2017)
Kampung Islam Kepaon (Islamic Village Kepaon) is an example of Islamic village. This village is locatedin Pemogan area. This village is trying to retain their identity in the middle of lifeâs complexities of Hinducommunity dominance. The trace record of the village is historical evidence that still exist in modern era. Thisresearch aims to know how the actualization of existing community in the village using Abraham Maslowconcept and Max Weberâs theory of Social Action. This research is a qualitative based research using singlecase studies. Observation, deep interview, and documentation by photograph are the tools for collecting data.The selected interviewees are the chief of the village, elders, and some selected individuals based on the genderand their active role. The results of this research show that the actualization of the Islamic community in thevillage is so powerful. There are a number of activities to actualize the existence of the villageâs communitieswho live side by side with the Hindu communities such as the tradition of ngejot, the rodat tradition at ProphetMuhammadâs Maulid ceremony, mekibung, reinforcement of the Balinese language as a form of emerging Balilocal wisdom, education-based Islamic, Rebana, and Bleganjur.Keyword : Actualization, Islam Village, Denpasar